Understanding the potential factors affecting carers' mental health during end-of-life home care: a meta synthesis of the research literature - Gunn Grande; Tracey Shield; Kerin Bayliss; Christine Rowland; Jackie Flynn; Penny Bee; Alexander Hodkinson; Maria Panagioti; Morag Farquhar; Danielle Harris; Alison Wearden (NIHR Journals Library, 2022)
Background: Family carers are central in supporting patients nearing the end of life, but this often has an impact on their own mental health. Understanding what factors may affect carers' mental health is important in developing strategies to maintain mental health, through identifying carers at risk who may need added monitoring and support or developing interventions to change modifiable factors. Reviews of the qualitative, observational and intervention literature were conducted to address this. Aims: (1) to review trials of carer interventions to improve our understanding of factors related to carer mental health identified in earlier qualitative and observational reviews; (2) to synthesise the evidence from our qualitative, observational and intervention reviews on factors related to carers' mental health during end-of-life caregiving. Method: We carried out searches of MEDLINE, Cumulative Index to Nursing and Allied Health Literature (CINAHL), PsycINFO® (American Psychological Association, Washington, DC, USA), Social Sciences Citation Index, EMBASE, Cochrane Central Register of Controlled Trials (CENTRAL) and Database of Abstracts of Reviews of Effects (DARE) from 1 January 2009 to 24 November 2019. We included studies into adult informal/family carers for adult patients at the end of life cared for at home that considered any factor related to carer mental health (anxiety, depression, distress, quality of life) pre bereavement. The quality appraisal used Critical Appraisal Skills Programme (CASP) checklists and the Newcastle-Ottawa Scale. The qualitative review analysis developed themes that then provided a framework for the quantitative review analyses. Findings from all three reviews were mapped onto a single framework, informed by a carer Review Advisory Panel. Results: A total of 31 qualitative, 60 observational, 12 intervention and 3 mixed-methods studies were identified. Factors associated with carer mental health were as follows: (1) patient condition, particularly psychological symptoms and quality of life; (2) impact of caring responsibilities, particularly life changes, workload and carer burden; (3) relationships, particularly with the patient; (4) finances, whether sufficient or not; (5) internal processes, particularly self-efficacy; (6) support, particularly adequacy and quality of support; (7) contextual factors, particularly age and gender. The three types of literature were reflected in most themes and yielded similar or complementary results, adding validity to findings. Only observational studies investigated contextual factors. Intervention studies focused on modifiable factors, but added little evidence on the causal direction between factors and mental health owing to design and analysis limitations. Relationships and finance received little attention overall. There was limited research into ethnicity, race or culture. Quantitative research missed some factors highlighted by carers in qualitative studies (e.g. quality aspects of formal support), and focused more on 'self-management' within internal processes (emphasised less by carers). Limitations: Findings are from Organisation for Economic Co-operation and Development (OECD) country English-language publications on adult carers and patients in the home setting and limited to these contexts. Literature heterogeneity (study focus, objectives, methods, variables, measures) hindered meta-synthesis. Conclusions: Future work requires broad stakeholder engagement to address the diverse range of factors associated with carers' mental health. Project findings will be disseminated accordingly. Future research needs more (1) work on defining and measuring concepts; (2) longitudinal design, repeated measurement and path analysis, to move beyond evidence of association towards an understanding of causal relationships; (3) focus on factors that matter to carers rather than what is easily measured or manipulated; and (4) investigation of relationships, finance, ethnicity, race and culture. Study registration: This study is registered as PROSPERO CRD42019130279. Funding: This project was funded by the National Institute for Health and Care Research (NIHR) Health and Social Care Delivery Research programme and will be published in Health and Social Care Delivery Research. See the NIHR Journals Library website for further project information.